2014
DOI: 10.1002/gcc.22179
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating soft tissue leiomyosarcoma and undifferentiated pleomorphic sarcoma: A miRNA analysis

Abstract: The rare and highly aggressive adult soft tissue sarcomas leiomyosarcoma (LMS) and undifferentiated pleomorphic sarcoma (UPS) contain complex genomes characterized by a multitude of rearrangements, amplifications, and deletions. Differential diagnosis remains a challenge. MicroRNA (miRNA) profiling was conducted on a series of LMS and UPS samples to initially investigate the differential expression and to identify specific signatures useful for improving the differential diagnosis. Initially, 10 high-grade LMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 33 publications
(37 reference statements)
2
43
0
2
Order By: Relevance
“…analysis, no effect of miR-199a-5p expression on patients' survival was detected, however, non-parametric correlation analyses demonstrated a correlation with tumor entity (P=0.014, Kruskal-Wallis test). This is concordant with the results of a previous study by Guled et al (28), describing a diagnostic role of miR-199-5p for the identification of undifferentiated pleomorphic sarcoma compared to leiomyosarcoma. It has also been demonstrated that low miR-199a-5p expression is associated with a poorer outcome in serous ovarian carcinoma (29), non-small cell lung carcinoma measured in patients' sera (30) and renal cell carcinoma (31).…”
Section: Discussionsupporting
confidence: 92%
“…analysis, no effect of miR-199a-5p expression on patients' survival was detected, however, non-parametric correlation analyses demonstrated a correlation with tumor entity (P=0.014, Kruskal-Wallis test). This is concordant with the results of a previous study by Guled et al (28), describing a diagnostic role of miR-199-5p for the identification of undifferentiated pleomorphic sarcoma compared to leiomyosarcoma. It has also been demonstrated that low miR-199a-5p expression is associated with a poorer outcome in serous ovarian carcinoma (29), non-small cell lung carcinoma measured in patients' sera (30) and renal cell carcinoma (31).…”
Section: Discussionsupporting
confidence: 92%
“…Expression of polo-like kinase 2 (PLK2) and miRs -100, -574, -22, -21 and -30 were negatively correlated with talazoparib sensitivity (Figure 6). MiR-22 is repressed in Ewing sarcoma expressing EWS-FLI1, and was low in leiomyosarcoma and miR-22 expression was negatively correlated with sensitivity to talazoparib (58). In addition, cMyc expression can produce a down regulation of miR-22 (59).…”
Section: Discussionmentioning
confidence: 99%
“…As regulators of gene expression, miRNAs are involved in regulating multiple biological processes, including cell growth, apoptosis, tissue growth, tissue morphogenesis and the regulation of tumor growth (17)(18)(19). Highly expressed in human endothelial cells, miR-126 is closely associated with several types of cancer and is possibly one of the future means for cancer treatment (4,20).…”
Section: Discussionmentioning
confidence: 99%